2018
DOI: 10.5812/jhealthscope.60531
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of an Ergonomic Chair for Students in Educational Settings

Abstract: Background: Proper designing of chairs based on ergonomics increases efficiency, promotes quality of education, leads to correct posture in students, and reduces risk of musculoskeletal disorders. Objectives: The aim of this study was to design and develop an ergonomic chair, based on anthropometric data of students in educational settings. Methods: Anthropometric parameters were obtained from a stratified-random sample of 207 students. The data were analyzed using the SPSS 20 software, and the results were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…The mismatch between chair width and buttock popliteal length leads students to have bad contact with backrest, so it causes pain in back and shoulders (Ansari, Nikpay and Varmazyar, 2018). The change of seat width size to be more ergonomic is needed due to the mismatch of chair width with poplitealto-buttock size.…”
Section: Chair Widthmentioning
confidence: 99%
See 1 more Smart Citation
“…The mismatch between chair width and buttock popliteal length leads students to have bad contact with backrest, so it causes pain in back and shoulders (Ansari, Nikpay and Varmazyar, 2018). The change of seat width size to be more ergonomic is needed due to the mismatch of chair width with poplitealto-buttock size.…”
Section: Chair Widthmentioning
confidence: 99%
“…This is in line with previous research which states that the backrest length is at least more than 95 percentile of the dimension of shoulder width (Pérez-gosende, 2017). Another study in Iran uses 95th percentile of the shoulder width for the backrest length proposed size (Ansari, Nikpay and Varmazyar, 2018). Moreover, research in India suggests a length of 420 mm (Wilson and Desai, 2017).…”
Section: Backrest Lengthmentioning
confidence: 99%
“…Various studies have shown that the ill-fitted design of classroom furniture have contributed to the high incidence of musculoskeletal disorders (MSDs) among school children (Musa & Ismaila, 2014). Improper design of chairs is one of the reasons of in appropriate sitting positions, which can lead to bad posture, fatigue, severe psychological stress and effects on students' performance (Ansari, et al, 2018). One more study demonstrated that wrongly designed school chairs and tables induce poor postures, leading to operational uneasiness and some musculoskeletal among students (Macedo et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the research is about designing classroom furniture to reduce the negative impact of poor posture in the classrooms [7]. Another research is about designing an ergonomic chair to reduce musculoskeletal disorders in students [8]. Work system improvement can also be made by changing the layout of facilities and by rearranging work equipment [9].…”
Section: Introductionmentioning
confidence: 99%